2022
DOI: 10.3390/foods11081083
|View full text |Cite
|
Sign up to set email alerts
|

Natural Pectin-Based Edible Composite Coatings with Antifungal Properties to Control Green Mold and Reduce Losses of ‘Valencia’ Oranges

Abstract: Novel pectin-based, antifungal, edible coatings (ECs) were formulated by the addition of natural extracts or essential oils (EOs), and their ability to control green mold (GM), caused by Penicillium digitatum, and preserve postharvest quality of ‘Valencia’ oranges was evaluated. Satureja montana, Cinnamomum zeylanicum (CN), Commiphora myrrha (MY) EOs, eugenol (EU), geraniol (GE), vanillin, and propolis extract were selected as the most effective antifungal agents against P. digitatum in in vitro assays. Pectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…This difference could be due to the time of application, as well as the need for lower concentrations of EOs when the application is carried out in preharvest. Nevertheless, contradictory results were observed in postharvest studies in oranges, where no effect on firmness was observed in oranges coated with a thymol solution [25,26]. Total soluble solids and titratable acidity results were in accordance with Pérez-Alfonso et al [21], where thymol and carvacrol were applied in postharvest to lemons and no changes were observed between the treated and control lemons.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…This difference could be due to the time of application, as well as the need for lower concentrations of EOs when the application is carried out in preharvest. Nevertheless, contradictory results were observed in postharvest studies in oranges, where no effect on firmness was observed in oranges coated with a thymol solution [25,26]. Total soluble solids and titratable acidity results were in accordance with Pérez-Alfonso et al [21], where thymol and carvacrol were applied in postharvest to lemons and no changes were observed between the treated and control lemons.…”
Section: Discussionsupporting
confidence: 57%
“…Previous in vitro studies have already evaluated the antifungal activity of Thymus and Oreganum species EOs at different concentrations (50-4000 µL/L) against P. digitatum, P. italicum, and G. citri-aurantii, achieving the best results when these cultures were subjected to the highest concentrations [14,[16][17][18][19]21,[23][24][25]43]. Further, the antifungal effect of the studied EOs when they were applied in postharvest fruits has also been widely studied in citrus against Penicillium spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, generally regarded as safe (GRAS) compounds have been widely tested (Palou et al., 2002; Venditti et al., 2005; Youssef, Ligorio, Sanzani, et al., 2012; Zhang & Swingle, 2003). Potassium sorbate (KS) is a GRAS compound that has been used as a preservative in foods and beverages, such as cheese, meat, sausages, yoghurt, juice, beer, and wine (Alvarez et al., 2022; Chahardoli et al., 2020; Mehyar et al., 2014; Sachis et al., 2016) with a limited development in citrus postharvest management. Despite this salt was classified as a minimal risk active ingredient and is exempt from residue tolerances, its popularity as a postharvest tool has been impaired due to its partial control efficacy (Gregori et al., 2008; Smilanick et al., 2008; Türkkan, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…EOs contain secondary metabolites produced in different parts of the plant, known to confer disease resistance, antioxidant and antimicrobial properties [32][33][34]. Their use as part of edible coating has been extensively studied to reduce weight loss, respiration rate and fungal decay in citrus fruit [35][36][37][38] and table grapes [39,40], among others. The synergic effect that major components of essential oils (eugenol, thymol, and carvacrol) have on the fungal spoilage of fruit has been previously demonstrated [38,41].…”
Section: Introductionmentioning
confidence: 99%